Providing A Person-Centred View: Applying Linked Data to Government Policy Reform and Service Design - Williams, Sharon; Cheng, Kenneth; Sipthorp, Mark (International Journal of Population Data Science, 2020)
The application of linked data by government has limited visibility due to complexities in publishing details of the analysis and interventions. The Victorian Department of Health and Human Services (DHHS) acknowledges the value of linked data in the department’s strategic plan, and linked data has been used in many policy reform and service design activities over the past three years. Introduction In 2016 the Centre for Victorian Data Linkage (CVDL), located in DHHS, developed the Victorian Linkage Map (VLM) of 20 plus health and human services datasets linked with births and deaths data. The VLM has since been expanded to include education, justice and police data. DHHS has been an “early adopter” in applying linked data to policy development, service reforms and departmental operations to improve the health and wellbeing of the Victorian population. Objectives and Approach The presentation will provide an overview of multi-sector data linkage in Victoria, and the value of frequent collaborations between CVDL and DHHS staff in applying linked data to priority projects and reforms. It will consider the challenges of cross-jurisdictional linkage in Australia, highlighting initiatives which are expanding linked datasets available to DHHS. Results DHHS has undertaken a broad range of linked data projects which have provided an evidence base for departmental activities, including provision of hospital, housing, health surveillance and child protection services. Linked data has also been used to develop an integrated demand model, which forecasts impact of investment in one program area on other parts of the service system. Conclusion / Implications The active use of linked data by DHHS provides a model for other government departments to improve service design and delivery to vulnerable populations. DHSS is expanding linked-data use to additional areas, and further imbedding in departmental operations.